Mesoporous titanium oxynitride monoliths from block copolymer-directed self-assembly of metal-urea additives - Li, Yun (2020)
This report describes a simple one-pot soft-templating and ammonolysis-free approach to synthesize mesoporous crystalline titanium oxynitride by combining block copolymer-directed self-assembly with metal sol and urea precursors. The Pluronic F127 triblock copolymer was employed to structure-direct titanium-oxo-acetate sol nanoparticles and urea-formaldehyde into ordered hybrid mesostructured monoliths. The hybrid composites were directly converted into mesoporous crystalline titanium oxynitride and retained macroscale monolithic integrity up to 800 °C under nitrogen. Notably, the urea-formaldehyde additive provided nitrogen and rigid support to the inorganic mesostructure during crystallization. The resultant mesoporous titanium oxynitride exhibited good electrochemical catalytic activity toward hydrogen evolution reaction in 1 M KOH aqueous medium under applied bias. Our results suggest an inexpensive and safe pathway to generate ordered mesoporous crystalline metal oxynitride structures suitable for catalyst and energy-storage applications.